Exploring the Determinants of Students Personal Financial Management: The Role of Social Environment, Spiritual Intelligence, and Lifestyle - Fauziah, Iis; Rahma, Aisatu; Agustin, Ayu; Ananda, Bunga Puja; Kustina, Lisa (Growth: Journal Management and Business, 2025)
This study aims to identify the influence of social environment, spiritual intelligence, and lifestyle on personal financial management. This study uses a quantitative approach aimed at identifying problems through data collection, compilation, and analysis. The population in this study were students of the Management Study Program, Class of 2022, Faculty of Economics and Business, Pelita Bangsa University. The number of samples in this study was 102 respondents. The analysis method used was multiple regression analysis, using the SPSS 26 program as a statistical test. The results of the study partially, Social environment and spiritual intelligence have a positive effect on personal financial management, while lifestyle has no effect on personal financial management. These findings highlight the importance of social and spiritual factors in shaping students’ financial behaviors, offering valuable insights for financial education strategies.